Seasonal variation of disease activity of systemic lupus erythematosus in Finland: a 1 year follow up study. Issue 11 (12th October 2004) - Hasan, T; Pertovaara, M; Yli-Kerttula, U; Luukkaala, T; Korpela, M
Abstract : Objectives: To study the role of different seasons in the disease activity of patients with systemic lupus erythematosus (SLE). Additionally, to evaluate whether the outdoor behaviour during the summer or a photoprovocation test affects disease activity. Methods: 33 patients with SLE were examined by a rheumatologist and a dermatologist at a university hospital in winter, spring, and summer. The activity of SLE was assessed by the ECLAM index. Their outdoor behaviour was recorded by a questionnaire during the summer. In the winter, 12 patients were photoprovoked by ultraviolet A and B radiation on a small skin area. Results: The ECLAM scores were higher in spring and tended to be higher in summer than in winter (p = 0.006 and p = 0.051). This finding, as well as the outdoor behaviour, were independent of the patients' own impression of their photosensitivity. Overall, the sun protection actions were inadequate. The photoprovocation had no statistical effect on disease activity, but one patient had a violent exacerbation of SLE manifestations shortly after the photoprovocation. Conclusions: In the northern climate SLE may be activated during the sunny season. Therefore, more effort should be focused on sun protection of patients with SLE.